2020
DOI: 10.17221/178/2020-pse
|View full text |Cite
|
Sign up to set email alerts
|

Improving the growth, lodging and yield of different density-resistance maize by optimising planting density and nitrogen fertilisation

Abstract: Matching the planting density, fertilisation, and genotype is crucial to improve the maize yield. Here, two-year field trials, including 4 densities and 3 nitrogen (N) rates for 2 maize cultivars, were conducted to study the effects of planting density and N rate on maize growth, lodging, spike characters, and yield. Compared with 360 kg/ha, N application of 180 kg/ha decreased the plant, ear height, and stem circumference of WeiKe 702 (WK702), while increased the plant height and stem circumference, but decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 23 publications
4
16
0
Order By: Relevance
“…Increasing planting density brings about ercer competition for solar radiation and other resources available of the individual plant, which results in the higher canopy morphology of PH, EH and GH. Our results are consistent with the previous results of Zhao et al, 31 who found that the PH and EH were enhanced with the planting density raised from 4.5 to 8.0 × 10 4 plant/ha under three N levels. As known, cultivars with high stalk and ear position are more susceptible to lodging due to higher plant gravity and enhanced upper fresh weight 21 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Increasing planting density brings about ercer competition for solar radiation and other resources available of the individual plant, which results in the higher canopy morphology of PH, EH and GH. Our results are consistent with the previous results of Zhao et al, 31 who found that the PH and EH were enhanced with the planting density raised from 4.5 to 8.0 × 10 4 plant/ha under three N levels. As known, cultivars with high stalk and ear position are more susceptible to lodging due to higher plant gravity and enhanced upper fresh weight 21 .…”
Section: Discussionsupporting
confidence: 93%
“…Stalk lodging induced bending and/or breakage of stems during maize growing season generally cause damages to vascular bundles 31 , and thereby prevent water transport from root to leaves and impair assimilates phloem transportation from the mesophyll into the stalk phloem, thus may allocating more photoassimilates to leaves or stalk than the ear 2,32 , hence affecting grain lling and decreased the kernel weight and effective ear number, that's why the decreased yield components of 100-grain weight and ear number were found in the less lodging-resistant hybrid of Xy335 in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Stalk lodging induces bending and/or breakage of stems during maize growth, generally caused by the damages to vascular bundles 28 , and thereby preventing water transport from root to leaves and impairing phloem transportation of assimilates from the mesophyll into the stalk phloem. Thus, more photoassimilates may be allocated to leaves or stalks than to the ear 2 , 29 , affecting grain filling and decreasing the kernel weight and effective ear number.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the density under the highest yield demonstrated by agronomists in the plant density experiments was taken as the optimal density. The experimental results of Zhao et al [28] in Kangcheng Village were adopted. The results of the two cultivars in 2015 and 2016 showed that the yield was the lowest when the density was 45,000 plants ha −1 .…”
Section: Measurement Methods Of Density Loss and Data Collectionmentioning
confidence: 99%
“…There is a need to enhance smallholder awareness and competencies and increase farmer confidence and willingness [10]. For example, it is important to improve farmer adoption of the optimal water and fertilizer management, pest control, chemical control and lodging prevention through field demonstration, education and training [51] in order to optimize the growth and development of maize and reduce the risk of lodging [28,52]. At the same time, this can reduce the plant density loss caused by other agronomic factors.…”
Section: Potential Optimization Approach Of Reducing Density Lossmentioning
confidence: 99%